ANTIBACTERY ACTIVITIES OF ETHANOL EXTRACT 70% KERSEN LEAVES (Muntingia calabura L.) ON THE BACTERIA Salmonella typhi - Ni Ima Wuri Handayani; Mukhamad Nur Khamid; Ambar Yunita Nugraheni (STIKES DUTAGAMA KLATEN, 2017)
Background: Typhoid fever is infectious disease caused by Salmonella typhi. The activity of Salmonella typhi can be blocked by antibacterial. Extracts of cherry leaves (Muntingia calabura L.) can be used for alternative medication because it contains of active substance as antibacterial. Objective: This research was aimed to investigate the antibacterial activity of 70% ethanol extracts of cherry leaves in resisting Salmonella typhi. Method: Cherry leaves were extracted by maceration method using 70% ethanol. The extract was determined by phytochemical screening using tube test. The determination of antibacterial activity uses Mueller Hinton which was done by Cup-Plate method. This research used various concentration such as 5.3% b/v, 17.6% b/v, 33.3% b/v and 53.8% b/v. Thick extract of cherry leaves was used as extract control, positive control used 250% of chloramphenicol while negative control used 250% of CMC-Na. Result: The result of the research showed that cherry leaves contain flavonoids, tannins, polyphenols and saponins. Minimum Inhibitory Concentration (MIC) toward Salmonella typhi is found at the concentration of 33,3% b/v in the 11,7 mm average of diameter inhibition zone. Conclusion: 70% ethanol extracts of cherry leaves has antibacterial activity in resisting Salmonella typhi.